2014
DOI: 10.1038/eye.2014.19
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish—on the move towards ophthalmological research

Abstract: Millions of people are affected by visual impairment and blindness globally, and the prevalence of vision loss is likely to increase as we are living longer. However, many ocular diseases remain poorly controlled due to lack of proper understanding of the pathogenesis and the corresponding lack of effective therapies. Consequently, there is a major need for animal models that closely mirror the human eye pathology and at the same time allow higher-throughput drug screening approaches. In this context, zebrafis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
114
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(127 citation statements)
references
References 115 publications
2
114
0
Order By: Relevance
“…Similar to humans, the zebrafish retina is composed of seven major cell types (Müller glia and six neural cell types), three nuclear layers separated by two plexiform layers, and a highly ordered mosaic of neurons in each layer [19,20]. As diurnal species, humans and zebrafish both have cone-dominant vision, in contrast to rod-dominant vision found in mice, which has advantages for studying cone degeneration diseases such as AMD [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to humans, the zebrafish retina is composed of seven major cell types (Müller glia and six neural cell types), three nuclear layers separated by two plexiform layers, and a highly ordered mosaic of neurons in each layer [19,20]. As diurnal species, humans and zebrafish both have cone-dominant vision, in contrast to rod-dominant vision found in mice, which has advantages for studying cone degeneration diseases such as AMD [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Retinal vasculopathies can be modeled by exposing animals to hypoxic water for 3-10 days to induce neovascularization and vascular leakage [21]. Similarly, exposure to glucose induces hyperglycemia, which has been shown to result in retinal structure abnormalities similar to those in DR [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes in the eye movements indicated that acute ethanol treatment may impair the vision function in zebrafish larvae. 13,32 D. Analysis of cardiac function in response to ethanol treatment…”
Section: Ethanol-induced Behavioral Responses Of Zebrafishmentioning
confidence: 99%
“…They also have small brains that are well suited to studies FIGURE 1.1: Top and side view of a 6 days post-fertilization (dpf) larvae zebrafish using light-based techniques. Despite the brain's size, larvae at 5 days postfertilisation (dpf) have functioning sensory systems for visual [11][12][13], auditory [14][15][16], somatory [17,18], water flow [19][20][21], and vestibular stimuli [22,23]. This makes them an ideal system in which to use light based tools to study the details of sensory neural circuits.…”
Section: Bfp Back Focal Planementioning
confidence: 99%